2016
DOI: 10.7717/peerj.1773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transport conditions for autologous bone marrow-derived mesenchymal stromal cells for therapeutic application in horses

Abstract: Background. Mesenchymal stromal cells (MSCs) are increasingly used for clinical applications in equine patients. For MSC isolation and expansion, a laboratory step is mandatory, after which the cells are sent back to the attending veterinarian. Preserving the biological properties of MSCs during this transport is paramount. The goal of the study was to compare transport-related parameters (transport container, media, temperature, time, cell concentration) that potentially influence characteristics of culture e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Regarding cell transportation, many studies have shown which are the shipping criteria that should be considered-for instance, supplementing media, transport temperature, and other variables, such as the type of container for the shipping. The latter did not show meaningful evidence; in detail, the use of plastic rather than glass containers did not show differences in terms of cell viability after 24 h at room temperature (20-22 • C) at several MSC concentrations [39]. Shipping temperature is up to cell storage conditions: frozen cells should be transported in dry ice around −80 • C, inside cryovials often wrapped with precooled material and placed in a leak-proof container to prevent direct contact of samples; otherwise, they can be transported in liquid nitrogen to maintain −196 • C temperature.…”
Section: Cryopreservationmentioning
confidence: 75%
See 1 more Smart Citation
“…Regarding cell transportation, many studies have shown which are the shipping criteria that should be considered-for instance, supplementing media, transport temperature, and other variables, such as the type of container for the shipping. The latter did not show meaningful evidence; in detail, the use of plastic rather than glass containers did not show differences in terms of cell viability after 24 h at room temperature (20-22 • C) at several MSC concentrations [39]. Shipping temperature is up to cell storage conditions: frozen cells should be transported in dry ice around −80 • C, inside cryovials often wrapped with precooled material and placed in a leak-proof container to prevent direct contact of samples; otherwise, they can be transported in liquid nitrogen to maintain −196 • C temperature.…”
Section: Cryopreservationmentioning
confidence: 75%
“…As a result, the majority agreed that MSC transport should be performed at 4 °C, which seems to be the most practical one. According to this, shipping fresh equine MSCs in isotonic saline solution at 4 °C within 24 h is considered ideal for immediate administration, although, in these conditions, MSC viability decreases up to 70% [ 39 , 40 , 43 ]. Only one study considered room temperature as superior in the case of short-duration transport [ 43 ].…”
Section: Mesenchymal Stromal Cells and Veterinary Regenerative Medmentioning
confidence: 99%
“…Compared to intravenous injection, subcutaneous injection and intramuscular injection require higher concentrated cell products with smaller volumes. As previous study has reported [28], MSCs suspension injected into small tendinous lesions would leak outside the defect and into the peritendinous tissue even the volume of cell suspension was only 1ml. Thus cell products of high cell concentration are needed.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 78%
“…Although cell viability in 20% HSA and 5% glucose in Ringer's lactate was high (>80%) till 48h, there was no research on the proliferation and immunosuppressive capacity of MSCs [21]. It has been reported that cell concentrations may affect biological properties of hematopoietic stem cells and cell viability of non-MSC cell lines [27,28]. Thus we also evaluated the effects of cell concentrations during short-term storage on the characteristics of MSCs.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Isolation and propagation of AMSCs from rats (11,12): Under sterile conditions, rats were euthanized with carbon dioxide (CO2), their abdomens were cut open and the adipose tissues were removed. After the adipose tissues were washed with saline solution, all the tissues were collected and incubated in Dulbecco's modified Eagle's medium (DMEM), (GIBCO/BRL) supplemented with 10% fetal bovine serum (FBS) (GIBCO/BRL).…”
Section: In Vitro Studiesmentioning
confidence: 99%